A Review of Synthetic Fiber Panel for Acoustic Properties - radzi, mustafa; Rosli, Mohd Arif; Mohd Sari, Kamarul Aini (Progress in Engineering Application and Technology, 2021)
The use of synthetic fibers has increased significantly since the 1960s, causing the natural fiber industry to lose most of its market share. A review on, synthetic fiber materials have been studied focusing on sound absorption coefficient. The objective of this study are to identify the previous research on acoustic panels based on synthetic fibers, to analyze the data of sound absorption coefficient based on density and thickness and to proposed the best synthetic fiber applied as an acoustic panel. There are ten articles with ten synthetic material being summarize and analyze. The result found that sound absorption coefficient of synthetic material increased with the increasing of density and thickness. The good sound absorber was polymer foam fiber mixed with natural fibers with sound absorption coefficient of 0.830 and 0.970 at low and high frequency. This synthetic material were proposed as the best materials to apply as acoustic panel and sound absorber.